The incidence of eating disorders in the UK in 2000–2009: findings from the General Practice Research Database - Irene Petersen; Nadia Micali; Janet L Treasure; Katrina W Hagberg (BMJ Open)
Objectives Few studies have investigated the incidence of eating disorders (EDs). Important questions about changes in the incidence of diagnosed disorders in recent years, disorder and gender-specific onset and case detection remain unanswered. Understanding changes in incidence is important for public health, clinical practice and service provision. The aim of this study was to estimate the annual (age-specific, gender-specific and subtype-specific) incidence of diagnosed ED: anorexia nervosa (AN), bulimia nervosa (BN) and eating disorder not otherwise specified (EDNOS) in primary care over a 10-year period in the UK (2000–2009); to examine the changes within the study period; and to describe peak age at diagnosis.Design Register-based study.Setting Primary care. Data were obtained from a primary care register, the General Practice Research Database, which contains anonymised records representing about 5% of the UK population.Participants All patients with a first-time diagnosis of AN, BN and EDNOS were identified.Primary outcome Annual crude and age-standardised incidence rates were calculated.Results A total of 9072 patients with a first-time diagnosis of an ED were identified. The age-standardised annual incidence rate of all diagnosed ED for ages 10–49 increased from 32.3 (95% CI 31.7 to 32.9) to 37.2 (95% CI 36.6 to 37.9) per 100 000 between 2000 and 2009. The incidence of AN and BN was stable; however, the incidence of EDNOS increased. The incidence of the diagnosed ED was highest for girls aged 15–19 and for boys aged 10–14.Conclusions The age-standardised incidence of ED increased in primary care between 2000 and 2009. New diagnoses of EDNOS increased, and EDNOS is the most common ED in primary care.